Last Glacial Maximum sea surface temperature and sea-ice extent in the Pacific sector of the Southern Ocean. (15th August 2016) - Benz, Verena; Esper, Oliver; Gersonde, Rainer; Lamy, Frank; Tiedemann, Ralf
Abstract: Sea surface temperatures and sea-ice extent are most critical variables to evaluate the Southern Ocean paleoceanographic evolution in relation to the development of the global carbon cycle, atmospheric CO2 and ocean-atmosphere circulation. Here we present diatom transfer function-based summer sea surface temperature (SSST) and winter sea-ice (WSI) estimates from the Pacific sector of the Southern Ocean to bridge a gap in information that has to date hampered a well-established reconstruction of the last glacial Southern Ocean at circum-Antarctic scale. We studied the Last Glacial Maximum (LGM) at the EPILOG time slice (19, 000–23, 000 calendar years before present) in 17 cores and consolidated our LGM picture of the Pacific sector taking into account published data from its warmer regions. Our data display a distinct east-west differentiation with a rather stable WSI edge north of the Pacific-Antarctic Ridge in the Ross Sea sector and a more variable WSI extent over the Amundsen Abyssal Plain. The zone of maximum cooling (>4 K) during the LGM is in the present Subantarctic Zone and bounded to its south by the 4 °C isotherm. The isotherm is in the SSST range prevailing at the modern Antarctic Polar Front, representing a circum-Antarctic feature, and marks the northern edge of the glacial Antarctic Circumpolar Current (ACC). The northward deflection of colder than modern surface waters along the South American continent led to a significant cooling of the glacial Humboldt Current surface waters (4–8 K), which affected the temperature regimes as far north as tropical latitudes. The glacial reduction of ACC temperatures may also have resulted in significant cooling in the Atlantic and Indian Southern Ocean, thus enhancing thermal differentiation of the Southern Ocean and Antarctic continental cooling. The comparison with numerical temperature and sea-ice simulations yields discrepancies, especially concerning the estimates of the sea-ice fields, but some simulations reproduce well our proxy-based temperature data. Highlights: Filling data gap in Southern Ocean LGM temperature and sea-ice reconstruction. Multi-parameter dating strategy to obtain highest possible age model accuracy. More uniform circum-Antarctic LGM cooling than previously proposed. Frontal system in the ACC strongly related to topographic and atmospheric forcing.